Charmed bones - Haines, Carolyn (Haines, Carolyn. Sarah Booth Delaney mystery., 2018)
"The next charming mystery from Carolyn Haines featuring spunky southern private investigator Sarah Booth Delaney. Private detective Sarah Booth Delaney doesn't quite know what to expect when she's urgently called to a school board meeting for Sunflower County, Mississippi. But she certainly wasn't expecting this: three Wiccan sisters are in the midst of a showdown with the Board of Education. They want to open a Wiccan school in Zinnia, Mississippi, and the conservative town vows to do anything necessary to stop them from opening their school. Sarah Booth and her partner in the detective agency, Tinkie Bellcase, are quickly enlisted to investigate the Wiccan sisters' real reasons for coming to town. Sarah Booth learns the sisters have rented a manor house and land from a reclusive local artist, Trevor Musgrove. But the case takes on a far more serious tone when Trevor Musgrove is found dead, and all evidence seems to point directly at the witch sisters"--